Research grants, sources of ideas and the effects on academic research - Hanna Hottenrott; Cornelia Lawson (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Based on a sample of research units in science and engineering at German universities, this study reports survey evidence showing that research grants impact research content. Research units that receive funds from industry are more likely to source ideas from the private sector. The higher the share of industry funding on the units' total budget, the more likely that large firms influenced the research agenda. Public research grants, on the other hand, are associated with a higher importance of conferences and scientific sources. What is more, the different sources of ideas impact scientific output. Research units that source research ideas from small and medium-sized firms (SMEs) patent more, but not more successful than others in terms of the impact of their inventions on future patents. If, on the other hand, research units source ideas from large firms we find them to publish less and with lower impact on future scientific work.
urn:nbn:de:bsz:180-madoc-324933
Keywords: C23; I23; O31; O34; O38; 330; University Research; Scientific Productivity; Research Funding; Academic Patents; Technology Transfer; Hochschulforschung; Forschungsfinanzierung; Sponsoring; Forschungssubvention; Patent; Technologietransfer; Deutschland